The Use of Formal Language Standards on Writing Thesis Report by The Library Science Undergraduate Students Faculty of Humanities Diponegoro University on Thesis Report Year 2010 -2014 - Jumino Jumino (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
The ability to search information is very important for students, especially when they write thesis. Whether they are able to understand information during the course of their studies is evident from the thesis reports they write. This article discusses how in the ability of student information search based on the thesis report of the Library Science Undergraduate students of Faculty of Humanities Diponegoro University, thesis reports 2010 to 2014. Methods of data collection done were documentation, then the data were processed by using qualitative methods to analyze the use formal language standard, report writing system, and thesis bibliography. The analysis result shows there are still many mistakes the students do in writing thesis. This indicates that there is still need for improvement and improvement of the system of teaching and writing guidance in order to obtain maximum results in writing thesis reports later on.Keywords: information search; formal language standard; writing system; thesis report